2014
DOI: 10.4103/0974-1208.142478
|View full text |Cite
|
Sign up to set email alerts
|

New laparoscopic peritoneal pull-through vaginoplasty technique

Abstract: BACKGROUND:Many reconstructive surgical procedures have been described for vaginal agenesis. Almost all of them are surgically challenging, multi-staged, time consuming or leave permanent scars on abdomen or skin retrieval sites.AIM:A new simple technique using laparoscopic peritoneal pull-through in creation of neo vagina has been described.MATERIAL AND METHODS:Total of thirty six patients with congenital absence of vagina (MRKH syndrome) were treated with laparoscopic peritoneal pull through technique of Dr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…2 The incidence is about 1 in 4000-5000 live female births. 1,2 The typical form is seen in 47% of patients, the atypical form in 21% and 32% present with the most marked form-the MURCS association which is an acronym for (MU)llerian, (R)enal, (C)ervicothoracic (S)omite abnormalities and is a developmental disorder that primarily affects the uro-genital system. (10) MRKH syndrome is associated with the Wnt family member 4 (Wnt4) mutation, LIM homeobox 1 (LHX1), HNF1 homeobox B (HNF1B) and T-box 6 (TBX6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The incidence is about 1 in 4000-5000 live female births. 1,2 The typical form is seen in 47% of patients, the atypical form in 21% and 32% present with the most marked form-the MURCS association which is an acronym for (MU)llerian, (R)enal, (C)ervicothoracic (S)omite abnormalities and is a developmental disorder that primarily affects the uro-genital system. (10) MRKH syndrome is associated with the Wnt family member 4 (Wnt4) mutation, LIM homeobox 1 (LHX1), HNF1 homeobox B (HNF1B) and T-box 6 (TBX6).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital absence of uterus, cervix and vagina is normally seen. 1 Total absence of Mullerian development will lead to aplasia, while the partial development which is a common occurrence leads to tubal and partial uterine development and complete absence of upper three fourth of vagina. 1 The main aim of treatment in MRKH syndrome patients is to solve problems of sexual life by reconstruction of the vagina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This surgical technique is comparatively simple with no morbidity. [ 21 ] It maintains self-respect and dignity of the patient, as it has no marks of surgery to declare and results in formation of normal vaginal lining. Peritoneal lining having the same parentage of Mullerian duct undergoes metaplasia and transforms itself into stratified squamous epithelium of normal vagina.…”
Section: Discussionmentioning
confidence: 99%
“…As the ovary became accessible per vaginum, three patients underwent ovum retrieval and pregnancy using surrogate mothers, making this a fertility-enhancing procedure. [ 21 ] We have demonstrated that peritoneal metaplasia is not from the simple multiplication of low cuboidal epithelium of peritoneum but complex phenomenon passing through activation followed by suppression of mesothelial progenitor cells.…”
Section: Discussionmentioning
confidence: 99%